Comparison of Clinical and Physiological Parameters for Benign Prostatic Hyperplasia in Hypertensive and Normotensive Patients - Zeng, Xian-Tao; Weng, Hong; Xiong, Jing; Huang, Qiao; Ma, Lin-Lu; Jin, Ying-Hui; Wang, Xing-Huan (Frontiers in Physiology, 2018)
Objective: To discover the correlation of clinical and physiological measures for benign prostatic hyperplasia in hypertensive and non-hypertensive patients. Methods: From September 2016 to October 2017, 435 patients were enrolled for further selection. The parameters evaluated for eligible patients included prostate volume, systolic blood pressure, diastolic blood pressure, international prostate symptom score, etc. Then the eligible patients were divided into two groups according to hypertension condition, and the clinical and physiological parameters were compared between two groups. The Pearson’s correlation coefficient was used to test the linearity of the relationships of these clinical and physiological components with prostate volume, total prostate specific antigen, and international prostate symptom score. Results: Finally, 350 patients were involved in this study, including 117 with hypertension and 233 without hypertension. Weight, body mass index, systolic blood pressure, and diastolic blood pressure were significantly different between the hypertension and non-hypertension groups. In the non-hypertension group, there were positive correlations between weight, body mass index, age and prostate volume; between fasting blood sugar, systolic blood pressure, diastolic blood pressure and total prostate specific antigen; between fasting blood sugar and international prostate symptom score. In the hypertension group, there were positive correlations between age and total prostate specific antigen and international prostate symptom score; between weight and prostate volume; between systolic blood pressure and total prostate specific antigen. Conclusion: This study indicated that there might be no significant association between hypertension and prostate volume.